2019
DOI: 10.1088/1741-2552/aafdca
|View full text |Cite
|
Sign up to set email alerts
|

Classification of motor imagery and execution signals with population-level feature sets: implications for probe design in fNIRS based BCI

Abstract: Objective. The aim of this study was to introduce a novel methodology for classification of brain hemodynamic responses collected via functional near infrared spectroscopy (fNIRS) during rest, motor imagery (MI) and motor execution (ME) tasks which involves generating population-level training sets. Approach. A 48-channel fNIRS system was utilized to obtain hemodynamic signals from the frontal (FC), primary motor (PMC) and somatosensory cortex (SMC) of ten subjects during an experimental paradigm consisting of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 57 publications
0
27
0
Order By: Relevance
“…fNIRS Data Acquisition fNIRS data was recorded using a continuous-wave system (NIRScout-816, NIRx, Medizintechnik GmbH, Berlin, Germany). The optode setup consisted of nine sources and eight detectors which were placed on the left hemisphere that cover areas commonly associated with motor imagery, i.e., premotor cortex and part of the supplementary motor area, primary motor cortex, somatosensory motor cortex and part of the parietal cortex following the extended 10/10 EEG system (see Figure 3; Sorger et al, 2012;Abdalmalak et al, 2016;Batula et al, 2017;Klein and Kranczioch, 2019;Erdogan et al, 2019). An in-house SDC was created by placing source S9 as close as the optodes would allow (∼13 mm away) to detector D5 on the same sagittal plane that connects D5 and source S6 (see Figure 3).…”
Section: Nested Menu and Error-correction Approachmentioning
confidence: 99%
“…fNIRS Data Acquisition fNIRS data was recorded using a continuous-wave system (NIRScout-816, NIRx, Medizintechnik GmbH, Berlin, Germany). The optode setup consisted of nine sources and eight detectors which were placed on the left hemisphere that cover areas commonly associated with motor imagery, i.e., premotor cortex and part of the supplementary motor area, primary motor cortex, somatosensory motor cortex and part of the parietal cortex following the extended 10/10 EEG system (see Figure 3; Sorger et al, 2012;Abdalmalak et al, 2016;Batula et al, 2017;Klein and Kranczioch, 2019;Erdogan et al, 2019). An in-house SDC was created by placing source S9 as close as the optodes would allow (∼13 mm away) to detector D5 on the same sagittal plane that connects D5 and source S6 (see Figure 3).…”
Section: Nested Menu and Error-correction Approachmentioning
confidence: 99%
“…The former, in particular, has been widely adopted since, unlike motor execution, motor imagery does not require intact thalamocortical tracts (Fernández-Espejo et al, 2015 ), making it preferable for patients with severe physical impairment. In previous fNIRS studies, classification accuracies in healthy controls have ranged from 63% to 98% (Coyle et al, 2004 , 2007 ; Sitaram et al, 2007 ; Erdoĝan et al, 2019 ). The discrepancy between studies is likely due to multiple factors.…”
Section: Introductionmentioning
confidence: 99%
“…This adds to the complexity of assessing residual brain function and raises an important question of whether the absence of brain function could result from detection insensitivity or fluctuations in awareness, rather than reflecting the absence of residual awareness. In addition to hardware improvements, more sophisticated machine learning approaches such as artificial neural networks (ANN) could help improve the sensitivity of fNIRS (Erdoĝan et al, 2019 ). Considering that fNIRS is portable, it has the advantage of testing at different times of the day and on multiple days to better capture a patient’s full state of awareness.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is highly portable and suitable for monitoring dynamic changes of oxygenation and deoxygenated hemoglobin concentration in brain tissue during movement and imagining; it has also been applied successfully in many fields [14][15][16][17][18][19][20][21][22][23]. Studies have shown that MI-BCI based on fNIRS (fNIRS-MI-BCI) is feasible and has several potential applications [24][25][26].…”
Section: Introductionmentioning
confidence: 99%